Work empowerment and burnout among registered nurses in two tertiary general hospitals - Xu Wang (2018)
Aims and objectives: To describe and explore the relationship between work empowerment and burnout as perceived by nurses in two tertiary general hospitals in China. Background: Studies conducted in Western countries show that work empowerment can negatively influence burnout. Review of literature indicates that currently, no study on the relationship between work empowerment and burnout has been conducted in China. Design: A correlational, cross-sectional design was adopted using questionnaires for data collection. Methods: This study used correlational and cross-sectional designs to collect and analyse data. The demographic data were analysed using frequency and percentage distributions. Work empowerment and burnout as perceived by registered nurses were analysed using means and standard deviation. The relationship between work empowerment and burnout was analysed using Spearman's rank-order coefficient after testing the normal distribution using the Kolmogorov-Smirnov test. Results: The registered nurses perceive work empowerment at a moderate level. Emotional exhaustion as determined in this study is higher than in other nursing studies. A negative correlation is indicated between work empowerment and emotional exhaustion. A statistically significant positive correlation is also indicated between work empowerment and personal accomplishment. Conclusion: When the work environment provides empowerment, registered nurses are less likely to experience burnout. Nursing supervisors should empower staff nurses by giving them opportunities to study, actualise the hospital's vision and share information with other staff nurses. Relevance to clinical practice: Nurse administrators can use the results of this study to develop policies, improve work empowerment programmes and decrease burnout so that staff nurses can work more effectively. © 2013 John Wiley & Sons Ltd.